2012
DOI: 10.4103/0975-9476.96528
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the effect of Isha Yoga on cardiac autonomic nervous system using short-term heart rate variability

Abstract: Background:Beneficial effects of Yoga have been postulated to be due to modulation of the autonomic nervous system.Objective:To assess the effect of Isha Yoga practices on cardiovascular autonomic nervous system through short-term heart rate variability (HRV).Design of the Study:Short-term HRV of long-term regular healthy 14 (12 males and 2 females) Isha Yoga practitioners was compared with that of age- and gender-matched 14 (12 males and 2 females) non-Yoga practitioners.Methods and Materials:ECG Lead II and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 18 publications
1
54
1
Order By: Relevance
“…The significant increase of post exercise value of mean R-R interval, SDNN, RMSSD was observed in this study which is consistent with findings of other researchers in healthy subjects after practicing yoga 23,24 . But some researchers reported about no significant change after breathing exercise in both healthy subjects and diseased condition 12,15,19,25 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The significant increase of post exercise value of mean R-R interval, SDNN, RMSSD was observed in this study which is consistent with findings of other researchers in healthy subjects after practicing yoga 23,24 . But some researchers reported about no significant change after breathing exercise in both healthy subjects and diseased condition 12,15,19,25 .…”
Section: Discussionsupporting
confidence: 82%
“…But some researchers found no significant change after breathing exercise in both healthy subjects and diseased condition 12,15,[22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Imbalances in these lead to cardiovascular disorders such as hypertension, ischemia, infarction, etc., Numerous studies indicate a strong association between compromised ANS (e.g., decreased vagal activity or increased sympathetic activity) and sudden and non-sudden cardiac death. [1]…”
Section: Introductionmentioning
confidence: 99%
“…[2] Lifestyle modifications are important factors in the treatment, prevention, and rehabilitation of cardiovascular disorders. [1] Yoga is one of the best lifestyle modifications and an ancient vedic science thought to have originated in India in 5000 BC which is being applied in the field of therapeutics. [34] It includes practice of specific posture ( āsana ), regulated breathing ( Prāṇāyāma) etc., Breath is the dynamic bridge between body and mind and Prāṇāyāma is one of the most important yogic practices.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Recently, evaluation of the higher-order spectra of HR patterns has shown that not only there are significant differences in them between rest and meditation, but also they are influenced by different types of meditation. [15] Muralikrishnan et al [16] investigated the effects of Isha Yoga on cardiac ANS activity. They found that the Isha Yoga practitioners had a well-balanced activity of vagal efferents, an enhanced HRV, and sympathovagal balance, compared to non-practitioners.…”
mentioning
confidence: 99%